JUMLAH LIMFOSIT PADA MODEL INFLAMASI SETELAH PEMBERIAN EKSTRAK GETAH BIDURI (Calotropis gigantea) - Meilawaty, Zahara (Fakultas Kedokteran Gigi Universitas Jember, 2011)
Background: Biduri many found in the region be in season drought, is a wild shrub. The sap contains bakteriolitik enzymes and proteolytic kalotropin enzymes papain-like. Biduri sap can be used as a toothache cure, heal ulcers and accelerate healing. Objective: to see the effect of extracts of sap of biduri against the number of lymphocytes in rat made gingival inflammation. Methods: The study used 36 wistar rats. All rat were given injury on their gingival using punch biopsy, further more divided into 4 groups, (1) control (-), given no medication; (2) control (+), given ibuprofen; (3) treatment group, given the extract of sap of biduri 50 mg / kg bw; (4) treatment group, given the extract of sap of biduri 500 mg / kg bw. Furthermore, each of 3 rats in all groups performed sacrificed on the 2nd, 4th, 8th dayâs after injury to take the mandible, after that the histological observation were done. The data were analyzed by two way Anova test, was continued by LSD test. Results: There were significant differences among the group for the number of lymphocytes in all groups (P<0.05). Conclusion: The extracts of biduri sap can reduce the number of lymphocytes.